Glioma-neuron interactions: insights from neural plasticity - Feng, Jingyu; Yang, Jun (Frontiers in Oncology, 2025)
The development of gliomas is linked to neuroplasticity. Neurons, which are largely nonregenerative in adulthood, rely on axons and synapses to rebuild the neural network in response to experience and injury. Neural stem cells and immune cells coordinate “creation” (e.g., neurogenesis) and “clearance” (e.g., synaptic pruning), guided by signals from neural circuits. This review summarizes neuroplasticity mechanisms and explores their connection to gliomas, revealing that glioma cells hijack neural network derived signals to promote growth, migration, and stem-like properties, while simultaneously disrupting normal neural conduction. Similar to oligodendrocyte precursor cells (OPCs), gliomas exploit neural network regulation but are prone to uncontrolled proliferation. Moreover, glioma induced neural hyperexcitability disrupts circuit homeostasis, creating a permissive microenvironment for glioma progression. Consequently, neuroplasticity will contribute to the study of glioma related mechanisms and the development of more targeted strategies for prevention and control.